Why is Binocular Rivalry Uncommon? Discrepant Monocular Images in the Real World - Arnold, Derek H. (Frontiers in Human Neuroscience, 2011)
When different images project to corresponding points in the two eyes they can instigate a phenomenon called binocular rivalry (BR), wherein each image seems to intermittently disappear such that only one of the two images is seen at a time. Cautious readers may have noted an important caveat in the opening sentence – this situation can instigate BR, but usually it doesn’t. Unmatched monocular images are frequently encountered in daily life due to either differential occlusions of the two eyes or because of selective obstructions of just one eye, but this does not tend to induce BR. Here I will explore the reasons for this and discuss implications for BR in general. It will be argued that BR is resolved in favour of the instantaneously stronger neural signal, and that this process is driven by an adaptation that enhances the visibility of distant fixated objects over that of more proximate obstructions of an eye. Accordingly, BR would reflect the dynamics of an inherently visual operation that usually deals with real-world constraints.